Draft genome sequences of multidrug resistant Staphylococcus arlettae isolated from cow nasal swab at Kelantan, Malaysia farm - Megat Zakaria, Puteri Nazurah; Zarizal, Suhaili; Mohamad, Noor Muzamil; Lean, Soo Sum; Mohd Desa, Mohd Nasir; Aklilu, Erkihun; Yeo, Chew Chieng (Chiang Mai University - Faculty of Veterinary Medicine, 2025)
Staphylococcus arlettae is an emerging opportunistic pathogen associated with bovine mastitis, a significant concern in animal health and milk production. This study investigates the genomic characteristics of a multidrug-resistant S. arlettae strain isolated from a healthy cow in Malaysia, providing crucial insights into its potential for pathogenicity and spread. The Staphylococcus arlettae BK2L15 isolate was obtained from a nasal swab of a healthy cow in Kelantan. Initial identification was based on its growth characteristics on Mannitol Salt Agar, followed by antimicrobial susceptibility testing using the disc diffusion method. Subsequent identification with matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry (MALDI-TOF/MS) confirmed the isolate as Staphylococcus arlettae, with a score value of 2.09. Whole genome sequencing was conducted using the Illumina MiSeq system, with raw read quality evaluated through QUAST and genome assembly performed using SPAdes v3.12.0. The Staphylococcus arlettae BK2L15 exhibited a multidrug resistance phenotype towards Erythromycin, Cefoxitin, Fusidic Acid, Oxacillin, Penicillin, Azithromycin and Amoxicillin. Whole genome analysis revealed a genome size of 2,699,512 bp with a GC content of 33.50%, assembled into two contigs. The genome comprises 2,915 protein-coding sequences includes all genomes features. The sequencing data of this strain provide a valuable reference for future fine-scale comparative genomic studies, facilitating the establishment of genomic relationships between lineages and enabling the prediction of virulence factors, mobile genetic elements, and antimicrobial resistance genes.